2017
DOI: 10.1021/acs.macromol.7b02328
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on Achiral-to-Chiral Transformation of Achiral Poly(diphenylacetylene)s via Thermal Annealing in Chiral Solvent: Molecular Design Guideline for Conformational Change toward Optically Dissymmetric Structures

Abstract: Achiral poly(diphenylacetylene)s (PDPAs: pMe3, pEt3, piPr3, pMe2O1, pMe2OD1, and mMe3) with different alkyl side chains at the para or meta position of the side phenyl ring were prepared to examine achiral-to-chiral transformations upon thermal annealing in a chiral solvent. All the para-substituted PDPAs showed significant circular dichroism (CD) enhancement upon annealing, whereas the meta-substituted polymer, mMe3, was inert to the same treatment. To investigate the kinetics, the asymmetric conformational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…However, the presence of a phenyl group on each carbon of the double bond in PDPAs makes the properties of both materials very different. For instance, PDPAs show better chemical, thermal and photochemical stability compared to PPAs [72–85] . Moreover, PDPAs exhibit another interesting property that PPAs do not have, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of a phenyl group on each carbon of the double bond in PDPAs makes the properties of both materials very different. For instance, PDPAs show better chemical, thermal and photochemical stability compared to PPAs [72–85] . Moreover, PDPAs exhibit another interesting property that PPAs do not have, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few examples related to chiral PDPAs [72–85] are found in the literature compared to the large amount of work that has been done with PPAs [12–33, 37–51, 94–97] . This is due to the difficulty of obtaining the former polymers in the laboratory by polymerization of the corresponding diphenylacetylene monomers (DPA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 These results suggest that the helix inversion energy of PDPAs is relatively high because of the steric repulsion between the pendant phenyl groups, and thermal annealing is necessary to induce a thermodynamically stable preferredhanded helical structure. 21,25,26 In addition, when these polymers were applied to CSPs for HPLC, (À)-h-poly-1S showed a higher chiral recognition ability toward many racemates than the as-prepared poly-1S with almost no helix-sense bias. Therefore, the one-handed helical structure induced in the polymer backbone plays an important role in the excellent chiral discrimination of PDPA-based CSPs.…”
Section: Introductionmentioning
confidence: 99%
“…By using a combination of 1 H and 13 C NMR, IR, Raman, VCD and ECD spectroscopies, they found that this polymer adopts a preferred cis‐transoidal structure, where P or M ‐helical senses can be induced by thermal annealing in water in the presence of chiral amines. On the other hand, in the case of asymmetric PDPAs, Kwak, Aoki and co‐workers made great contributions to the study of their luminescent properties and to the achiral‐to‐chiral transformations of PDPAs [78, 82, 85–89] . To perform these studies, a catalyst developed by Masuda [TaCl 5 ‐n‐Bu 4 Sn] was used [77] .…”
Section: Introductionmentioning
confidence: 99%